Comprehensive TCR repertoire analysis of CD4+ T-cell subsets in rheumatoid arthritis. Issue 109 (May 2020) - Jiang, Xu; Wang, Shiyu; Zhou, Chen; Wu, Jinghua; Jiao, Yuhao; Lin, Liya; Lu, Xin; Yang, Bo; Zhang, Wei; Xiao, Xinyue; Li, Yueting; Wu, Xunyao; et al.
Abstract: The pathogenesis of rheumatoid arthritis (RA), a systemic autoimmune disease characterized by autoreactive T-cell accumulation and pro-inflammatory cytokine overproduction, is unclear. Systematically addressing T-cell receptor (TCR) repertoires of different CD4 + T-cell subsets could help understand RA pathogenesis. Here, peripheral CD4 + T cells from treatment-naïve RA patients and healthy controls were sorted into seven subsets including naïve, effector, central memory, effector memory (EMT), Th1, Th17, and regulatory T cells. T-cell receptor β chain repertoires were then analyzed by next-generation sequencing. We identified T-cell clonal expansion in EMT and Th17 cells of RA patients, with highly similar TCR repertoires. Ex vivo experiments demonstrated the preferred differentiation from EMT to Th17 cells in RA. Notably, we showed that TCR diversity and abundance of differentiated T cells of Th17 were significantly correlated with RA disease activity. Based on these observations, we propose that abnormal differentiation from EMT to Th17 and expansion of Th17 play pivotal role in RA pathogenesis. Highlights: The abnormal uses of TRBV3-1 and TRBJ2-7 genes are detected in effector memory T (EMT) and Th17 cells in rheumatoid arthritis (RA) patients. The T-cell receptor (TCR) repertoire diversities of EMT and Th17 cells are decreased in RA patients. Stronger correlations between EMT and Th17 cells exist in RA patients. Ex vivo experiments demonstrate the preferred differentiation from EMT to Th17 cells in RA. Clonotypes of Th17 cells differentiated from EMT correlated with RA disease activity.